Anticholinergic and Sedative Medications Are Associated With Neurocognitive Performance of Well Treated People With Human Immunodeficiency Virus. (2nd September 2022) - Jakeman, Bernadette; Scherrer, Alexandra U; Darling, Katharine E A; Damas, Jose; Bieler-Aeschlimann, Melanie; Hasse, Barbara; Schlosser, Ladina; Hachfeld, Anna; Gutbrod, Klemens; Tarr, Philip E; Calmy, Alexandra; Assal, Frederic; et al.
Abstract: Background: We previously showed that anticholinergic (ACH) medications contribute to self-reported neurocognitive impairment (NCI) in elderly people with human immunodeficiency virus (PWH). The current cross-sectional study further evaluated the effect of ACH and sedative drugs on neurocognitive function in PWH who underwent comprehensive neuropsychological evaluation. Methods: A medication review was performed in PWH enrolled in the prospective Neurocognitive Assessment in Metabolic and Aging Cohort within the Swiss HIV Cohort Study. Neurocognitive functions were analyzed in 5 domains (motor skills, speed of information, attention/working memory, executive functions, and verbal learning memory). The effect of ACH and sedative medications on neurocognitive functioning was evaluated using linear regression models for the continuous (mean z-score) outcome and multivariable logistic regression models for the binary (presence/absence) outcome. Results: A total of 963 PWH (80% male, 92% Caucasian, 96% virologically suppressed, median age 52) were included. Fourteen percent of participants were prescribed ≥1 ACH medication and 9% were prescribed ≥1 sedative medication. Overall, 40% of participants had NCI. Sedative medication use was associated with impaired attention/verbal learning and ACH medication use with motor skills deficits both in the continuous (mean z-score difference −0.26 to −0.14, P < .001 and P = .06) and binary (odds ratio [OR], ≥1.67; P < .05) models. Their combined use was associated with deficits in overall neurocognitive functions in both models (mean z-score difference −0.12, P = .002 and OR = 1.54, P = .03). These associations were unchanged in a subgroup analysis of participants without depression ( n = 824). Conclusions: Anticholinergic and sedative medications contribute to NCI. Clinicians need to consider these drugs when assessing NCI in PWH. Abstract : Non-HIV medications contribute to neurocognitive impairment in well treated people with HIV. Anticholinergic and sedative medications impair motor skills and attention/verbal learning, respectively. Their combined use impairs overall neurocognitive functions. Clinicians need to consider these medications when assessing neurocognitive impairment.